The Integration of Urban Agriculture into Sustainable City Development. A Case Study of Accra and Kumasi Cities - Tornyie, Edem Kwame (2011)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in Partial Fulfillment for the Requirements for a Degree of MASTER OF SCIENCE (Development Planning and Management)